Sintesis Lintas Sektor Untuk Meningkatkan Ketahanan Pangan dan Mengurangi Stunting di Nagari Gantiang Mudiak Utara Surantih Kecamatan Sutera Pesisir Selatan - Wahyuni, Fitri; Yusran, Rahmadani (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2025)
This study focuses on cross-sectoral synthesis to improve food security and reduce stunting in Nagari Gantiang Mudiak Utara Surantih, Sutera District, Pesisir Selatan Regency. This study uses a descriptive qualitative approach with interviews and documentation as a means of data collection. Data analysis is carried out through data reduction, data presentation, and drawing conclusions. This study refers to the family food security policy stated in the Pesisir Selatan Regency Regional Regulation No. 1 of 2019 concerning food security. The research findings show that the driving factors for the role of cross-sectors in supporting family food security in preventing stunting are the existence of clear duties and functions from related agencies and the existence of food security regulations in the form of Regional Regulation No. 1 of 2019, which supports cross-sectoral synergy. However, the role of cross-sectors in family food security also experiences obstacles, namely low food diversification capabilities, lack of cross-sectoral involvement in program supervision and evaluation, ineffective coordination, and limited budget allocation. Therefore, a flexible approach is needed to the needs and characteristics of each region in order to achieve optimal results in realizing sustainable family food security and preventing stunting.